Successful implementation of the shrimp farmers Kamphaeng Saen Nakhon Pathom. - Srathonghoum, Pataraporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purpose of this research are 1) To Study the success of the shrimp farmers Kamphaeng Saen Nakhon Pathom. 2) Compare success of the shrimp farmers Kamphaeng Saen Nakhon Pathom by classified according to personal factors. 3) To Study guidelines the success of the implementation of the shrimp farmers Kamphaeng Saen Nakhon Pathom. The sample group of 313 shrimp farmers by stratified random sampling and 10 interviewes were selected by purposive sampling. The research instrument are questionnaire and interview. Statistic in this research used the frequency, percentage, mean, standard deviation, t-test and one-way analysis of variance and content analysis. The research result finds that : 1) The success of the shrimp farmers Kamphaeng Saen Nakhon Pathom, the overall and each aspect were at the high level. The highest level was Financial, internal process, Learning and Development And the last is the customer. 2) Farmers who have sex, education level and experience to differ,their are opinions on the success of the implementation is no different. And farmers who have age and locations to differ,there are opinions on the success of the operation is different. A statistically significant at the .05 3) The success of the implementation of shrimp farmers, farmers should prepare financial accounts and transaction costs between the Shrimp farming. Such as note from the pond preparation. shrimp purchase, food, workers, the oil until the catch shrimp. To clearly separate the income that must be spent in any way. The customers, farmers should learn more about the nutrients that are beneficial. The transfer of pond water to increase oxygen. The addition of minerals in the pond. The Internal process, farmers should have more contact with government agencies. May be of guidance in shrimp to information that is useful to the shrimp or have contact with the private sector, who came to the knowledge of the shrimp. Learning and development farmers should learn from farmers together or attend a workshop on the shrimp. Article history : Accepted 18 April 2017 SIMILARITY INDEX = 0.00